Basal Exposure Therapy: A New Approach for Treatment-Resistant Patients with Severe and Composite Mental Disorders - Heggdal, Didrik; Fosse, Roar; Hammer, Jan (Frontiers in Psychiatry, 2016)
New treatment approaches are needed for patients with severe and composite mental disorders who are resistant to conventional treatments. Such treatment-resistant patients often have diagnoses of psychotic or bipolar disorders or severe personality disorders and comorbid conditions. In this study, we evaluate basal exposure therapy (BET), a novel ward-integrated psychotherapeutic approach for these patients. Central to BET is the conceptualization of undifferentiated existential fear as basic to the patients’ problem, exposure to this fear, and the therapeutic platform complementary external regulation, which integrates and governs the totality of interventions throughout the treatment process. BET is administered at a locked-door ward with 6 patient beds and 13.5 full-time employees, including a psychiatrist and 2 psychologists. Thirty-eight patients who had completed BET were included, all but two being female, mean age 29.9 years. Fourteen patients had a diagnosis of schizophrenia or schizoaffective disorder (F20/25), eight had bipolar disorder or recurrent depressive disorder (F31/33), eight had diagnoses in the F40–48 domain (neurotic, stress-related, and somatoform disorders), five were diagnosed with emotionally unstable personality disorder (F60.3), and three patients had other diagnoses. Twenty of the patients (53%) had more than one ICD-10 diagnosis. Average treatment time in BET was 13 months, ranging from 2 to 72 months. Time-series data show significant improvements in symptoms and functioning from enrollment to discharge, with effect sizes at 0.76 for the Dissociation Experience Scale, 0.93 for the Brief Symptom Inventory, 1.47 for the Avoidance and Action Questionnaire, and 1.42 and 1.56, respectively, for the functioning and symptom subscales of the Global Assessment of Functioning Scale. In addition, the patients used significantly less antiepileptic, antipsychotic, anxiolytic, and antidepressant medications at discharge than at treatment enrollment. Patient improvement across treatment was associated with the following duration of time in BET, the successful completions of the exposure component of BET, positive changes in experiential avoidance as measured with the Acceptance and Action Questionnaire, and high symptom levels and low levels of functioning at treatment start. The findings indicate that BET may be a promising inpatient psychotherapeutic approach for previously treatment-resistant patients with severe and comorbid conditions.